Ideological presentations in official promotion of intangible cultural heritage (ICH) on short-form video platforms: a multimodal content analysis - Liu, Ruoxi; Qiu, Haoran (Information Research an international electronic journal, 2025)
Introduction. This study investigates what ideological themes are embodied in the official promotion of intangible cultural heritage (ICH) on short-form video (SFV) platforms, and further examines how these ideological themes are presented through various content creation elements. Method. Two trained researchers in information sciences conducted a multimodal content analysis of 532 SFVs downloaded from a nationally representative official Douyin (the Chinese version of TikTok) account promoting ICH. Findings. This study identified four primary ideological themes embodied in the official promotion of ICH: (1) cultural democratization, (2) tradition revivalism, (3) patriotism, and (4) multiculturalism. Moreover, we revealed the distribution of content creation elements across SFVs reflecting various ideological themes. Conclusion. In SFV platforms like Douyin, ICH promotion highlights grassroots-centered narratives and user-generated videography. Traditional and popular culture are integrated within this context. This fosters a relatively democratized discourse around ICH, creating a more inclusive and softened ideological expression.